(untitled) (Mustansiria Dental Journal, 2018)
To determine the extent of temporomandibular joint (TMJ) involvement in patients with rheumatoid arthritis compared with a matched control group. And to evaluate the correlation between clinical findings and radiographical findings. The studied sample comprised 50 patients with rheumatoid arthritis, age ranged from 18 to 72 years with the mean age of 40.98 (± 13.67.The control group consisted of 63 subjects age–matched non rheumatic patients: Each patient was informed about the purpose of the investigation and that it would include questionnaire, clinical and radiographical examinations. The radiographic examination was done by using double TMJ lateral panoramic technique. It was found that 64% of RA patients complained of two or more clinical signs and symptoms compared with 44% of the control group ,the difference was statistically significant (P< 0.05), the most important clinical findings were pain on palpation and on opening and closing, crepitation, limitation of jaw opening and morning stiffness, difference were statistically significant (P< 0.05). Among the clinically involved subjects in study RA group 28 subjects (56%) had bilateral involvement, 3 subjects (6%) had right side involved and 1 subject (2%) had only left side involvement. The radiographic involvement of TMJ was found in 16 subjects (32.0 %) of the study group compared with 1subject (1.6 %) of the control group. There is a highly statistically significant difference between the study group and the control group (P< 0.05); the most common radiographical finding was erosion. Complete condylar destruction was found in 1 patient which resulted in anterior open bite. Among involved cases 11 subjects (22%) had bilateral involvement, 5 subjects (10%) had unilateral involvement (3subjects (6%) had left side involved and, 2 (4 %) subjects had only right side involved. There was no correlation between clinical and radiographic find ings. There was correlation between the extent of radiographical findings and duration of Rheumatoid Arthritis p value (P< 0.05).The clinical and radiographic findings were more common in RA group than in control individual. The clinical and radiographic findings are not always bilateral in TMJs of patients with rheumatoid arthritis. Key words: TMJ disorders, TMJ